SYNTHESIS OF BACTERICIDAL MICROFILTRATION CERAMIC MEMBRANES: Received: 01st September 2021; Revised: 25th November 2021, 11th December 2021, 29th January 2022; Accepted: 05th February 2022 - Serhiienko, Alla O; Dontsova, Tetiana A; Vorobyova, Victoria I (MATTER: International Journal of Science and Technology, 2022)
Membrane technologies have become widely used in filtration and separation processes in chemical, oil, food, pharmaceutical, medical, environmental, textile industries, etc. Recently, there is a growing demand for the use of bactericidal membranes due to their effectiveness in neutralizing microorganisms. The aim of this work is to synthesize microfiltration ceramic membranes modified with silver nanoparticles to provide them with bactericidal properties. In this work, ceramic membranes are synthesized by dry pressing followed by sintering from natural raw materials of Ukrainian origin, namely: kaolin and saponite, as well as with the addition of silicon carbide, sodium silicate, and calcium carbonate. To provide ceramic membranes with bactericidal properties, they were modified with particles of silver. The synthesized ceramic membranes were characterized by X-ray diffraction and fluorescence analysis, and their bactericidal ability has been established. The ceramic filtration membranes after modification by silvers exhibited an inhibitory effect on the growth of Gram-positive (B. subtilis.) and Gram-negative (Escherichia coli) pathogens. Thus, the obtained bactericidal ceramic membranes are of great interest for their use for biofouling control.